2018
DOI: 10.1103/physrevc.97.054617
|View full text |Cite
|
Sign up to set email alerts
|

Optical model potential analysis of n¯A and nA interactions

Abstract: We use a momentum-dependent optical model potential to analyze the annihilation cross sections of the antineutronn on C, Al, Fe, Cu, Ag, Sn, and Pb nuclei for projectile momenta p lab 500 MeV/c. We obtain a good description of annihilation cross section data of Barbina et al. [Nucl. Phys. A 612, 346 (1997)] and of Astrua et al. [Nucl. Phys. A 697, 209 (2002)] which exhibit an interesting dependence of the cross sections on p lab as well as on the target mass number A.We also obtain the neutron (n) non-elastic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…[3]) revealed that the annihilation cross sections of n, and p, on C nuclei at low energies, appear to follow a similar trend with only minor differences. Much curious about the puzzle, we recently introduced a new momentum-dependent optical potential to investigate the behavior of the annihilation cross-sections for the n, and the p, on C, Al, Fe, Cu, Ag, Sn, and Pb nuclei in the momentum range 50 − 500 MeV/c [26], via the ECIS code [27]. The calculated results were concordant with the OBELIX's annihilation cross-section data [16,17].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…[3]) revealed that the annihilation cross sections of n, and p, on C nuclei at low energies, appear to follow a similar trend with only minor differences. Much curious about the puzzle, we recently introduced a new momentum-dependent optical potential to investigate the behavior of the annihilation cross-sections for the n, and the p, on C, Al, Fe, Cu, Ag, Sn, and Pb nuclei in the momentum range 50 − 500 MeV/c [26], via the ECIS code [27]. The calculated results were concordant with the OBELIX's annihilation cross-section data [16,17].…”
Section: Introductionmentioning
confidence: 62%
“…However, we shall follow a collection of WKB works for complex-potential scattering by Brink, Takigawa, Lee, Marty, and Ohkubo [37][38][39] as they deemed proper for the present analyses. We adapt the same momentum-dependent optical potential used in our earlier work [26] in the present semiclassical theory. We consider the concept of the interference between a barrier wave reflected at the potential barrier and modified by the tunneling effect, and an internal wave which penetrates the barrier, into the potential pocket, and reemerges through the barrier out to r → ∞.…”
Section: Semiclassical Analyses Of the Annihilation Oscillations And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Wong and Li proposed [89] a new manyparameter potential which describes well the existing experimental data on antinucleon-nucleus annihilation. No comparison with other energy level shifts and widths of atomic levels and differential elastic cross section was presented in the article.…”
Section: B Choice Of Parameters In Optical Potentialsmentioning
confidence: 83%
“…Recently, Wong and Li proposed [89] a new many parameter potential which describes well the existing experimental data on antinucleon-nucleus annihilation. No comparison with other energy level shifts and widths of atomic levels and differential elastic cross section was presented in the article.…”
Section: B Choice Of Parameters In Optical Potentialsmentioning
confidence: 84%